Testimony through culture: towards a theoretical framework. Issue 3 (3rd July 2019) - Jones, Sara
ABSTRACT: This article brings together approaches from a range of disciplines to explore how we might approach testimony as it is produced through culture. It examines how we can define and understand the diverse forms of witnessing that are produced in artistic works and everyday practices such as education and law. With a focus on the witness to atrocity, the article develops a theoretical framework for the study of testimony through culture. It highlights the importance of focusing on the 'witnessing text' and the relationship between text and audience. Authenticity is thus understood as a process based on trust and acknowledgement, which can explain our reluctance to accept perpetrator testimony. Nonetheless, allowing perpetrators to speak and engaging with perpetrator texts through 'other-oriented empathy' is essential if we are to fully understand and prevent mass violence. Authenticity and empathy are also key terms in our engagement with secondary witnesses. Reflection on what it means to 'know' violence can help us unpick the relationship between ethical approaches to the mediation of testimony and the response elicited by 'fake' testimonies. Ultimately, I conclude that fictionalisation of testimony is legitimate, but that it gives rise to ethical questions relating to the purpose of that mediation.